Immune Dysfunctions of CD56neg NK Cells Are Associated With HIV-1 Disease Progression - Cao, Wen-Jing; Zhang, Xiao-Chang; Wan, Lin-Yu; Li, Qing-Yu; Mu, Xiu-Ying; Guo, An-Liang; Zhou, Ming-Ju; Shen, Li-Li; Zhang, Chao; Fan, Xing; Jiao, Yan-Mei; Xu, Ruo-Nan; et al. (Frontiers in Immunology, 2022)
Background Populations of natural killer cells lacking CD56 expression [CD56neg natural killer (NK) cells] have been demonstrated to expand during human immunodeficiency virus (HIV)-1 infection. However, their phenotypic and functional characteristics have not been systematically analyzed, and their roles during disease progression remain poorly understood. Methods In this study, 84 donors, namely 34 treatment-naïve HIV-1-infected patients (TNs), 29 HIV-1-infected patients with successful antiretroviral therapy (ARTs), and 21 healthy controls (HCs), were enrolled. The phenotypic and functional characteristics of CD56neg NK cells were analyzed using single-cell RNA-sequencing (scRNA-seq) and flow cytometry. A potential link between the characteristics of CD56neg NK cells and the clinical parameters associated with HIV-1 disease progression was examined. Results The frequency of the CD56neg NK cell population was significantly increased in TNs, which could be partially rescued by ART. Flow cytometry analyses revealed that CD56neg NK cells were characterized by high expression of CD39, TIGIT, CD95, and Ki67 compared to CD56dim NK cells. In vitro assays revealed reduced IFN-γ and TNF-α secretion, as well as decreased expression of granzyme B and perforin in CD56neg NK cells. In line with the data obtained by flow cytometry, scRNA-seq analysis further demonstrated impaired cytotoxic activities of CD56neg NK cells. Notably, a negative correlation was observed between CD39, CD95, and Ki67 expression levels in CD56neg NK cells and CD4+ T cell counts. Conclusions The results presented in this study indicate that the CD56neg NK cell population expanded in HIV-1-infected individuals is dysfunctional and closely correlates with HIV-1 disease progression.